MODEL OF LOCAL CAPACITY DEVELOPMENT FOR THE TROPICAL DISEASES HANDLING IN EAST JAVA - Hendrarti, Dwi Windyastuti Budi; Wicaksono, Dimas Aryo; Dewi, Yulis Setiya; Srianto, Puji (Indonesian Journal of Tropical and Infectious Disease, 2017)
Indonesia is a tropical country with its all potential for tropical diseases that are vulnerable to attack its population. This study aims to identify the mechanisms of the tropical disease handling and the potentials that can be done to increase the capacity of tropical disease handling itself. The focus of this research is to increase the capacity of the tropical diseases handling existing in East Java, more specifically in some regencies or cities, among others are Bojonegoro, Sampang and Pacitan. The approach of the study was the qualitative approach which was characterized by the existence of an actual setting, researchers as a key instrument, emphasizing the process, and the data analysis is inductive. Data were collected using in-depth interview has well as secondary data from health care institution and the internet. A focused group discussion was also occupied to enrich the results, the cases were illustrated and the models were structured more comprehensively in the handling of tropical diseases. Participants of this study were health care workers who work at the health institutions including the Health Department, Hospitals, the and Public Health Centers. The findings were all analyzed qualitatively. The results of this study indicated that there are four dimensions of capacity, namely the capacity of the human resource, the capacity of the institution, the capacity of the system and the capacity of the community or the community itself.